Pendampingan Pendalaman Materi Matematika Berbasis Etnomatematika untuk Siswa Kelas VII SMPN 2 Sekampung Udik - Endah Wulantina; Juitaning Mustika; Annisa Annisa (Pusat Pengabdian Masyarakat (PPM) Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam Negeri (IAIN) Metro, 2022)
Learning conducted online during the pandemic caused several problems for schools in areas where internet access was difficult, including students finding it difficult to understand the material, especially mathematics subjects because they quickly got bored and did not get all the material in the curriculum. This service will link mathematics with culture which is called ethnomathematics. The purpose of this service is to assist students in understanding mathematical material by assisting in an effort to deepen mathematics material for seventh grade students at SMPN 2 Sekampung Udik, East Lampung. The implementation method uses participatory action research (PAR) with stages in the form of preparation, implementation, evaluation and reflection. The culture used and closer to the subject of mentoring is the local culture of Lampung in the traditional game Taplak / Suksuk Lampung on a flat wake. This mentoring activity went well and received a positive response from participants and teachers